Fixed-term employment, work organization and job satisfaction: Evidence from German individual-level data - Michael Beckmann; Thomas Cornelissen; Bernd Schauenberg (University of Basel, Center of Business and Economics (WWZ), 2009)
The present paper examines the joint effect of fixed-term employment and work organization on job satisfaction using individual-level data from the German Socio-Economic Panel (GSOEP). Specifically, we analyze whether workers who are heterogeneous in terms of the type of working contract (fixed-term vs. permanent) do also differ with regard to job satisfaction, when they perform under comparable work organizational conditions. Such information would be quite valuable for employers, because they can learn about the responsiveness of heterogeneous workers to innovative work organizational practices. For this purpose, we at first estimate a linear fixed effects model, thereby controlling for unobserved time-constant characteristics. In a second step, we account for potential remaining endogeneity by combining the fixed effects approach with a two-stage estimation strategy. Our empirical results show that in terms of job satisfaction fixed-term workers and their permanent counterparts respond differently to a number of organizational practices including task diversity, employee involvement, social relations at work, general working conditions, and career prospects. The results may be used by employers to improve their concept of diversity management and specifically the job design of heterogeneous workers.
Keywords: J28; J81; M55; 330; Fixed-term employment; permanent employment; job satisfaction; work organization; selectivity bias; unobserved heterogeneity; Befristete Beschäftigung; Arbeitsorganisation; Arbeitszufriedenheit; Leistungsmotivation; Schätzung; Deutschland